2003
DOI: 10.1515/znc-2003-3-420
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin-Protector against Oxidative Stress and Regulator of Glycolysis in Human Erythrocytes

Abstract: Fe-lactoferrin to its receptors. Lactoferrin (50 and 100 nm), similar to ferricyanide, increased the accumulation of lactate (respectively by 25% and 30%). These results support the assumption that ferricyanide and lactoferrin are final acceptors of a common electron transport chain connected with the regulation of glycolysis. We established an antioxidative effect of lactoferrin on erythrocytes, which was expressed as: a) an influence on content and on activity of intracellular antioxidants Ð namely an enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 1 publication
1
30
0
Order By: Relevance
“…Its antioxidant 20 and anti-inflammatory activities (blocking nuclear factor-kB activation in response to LPS 16 ) could explain the positive effects of lactoferrin in intracellular insulin action. LPS-stimulated THP-1 conditioned media induced a significant decrease in response to insulin in HepG2, 3T3-L1 fibroblasts and in pre-differentiated (after INS-DEX-IBM mixture) 3T3-L1 cells, as demonstrated by decreased insulin-induced 473Ser AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Its antioxidant 20 and anti-inflammatory activities (blocking nuclear factor-kB activation in response to LPS 16 ) could explain the positive effects of lactoferrin in intracellular insulin action. LPS-stimulated THP-1 conditioned media induced a significant decrease in response to insulin in HepG2, 3T3-L1 fibroblasts and in pre-differentiated (after INS-DEX-IBM mixture) 3T3-L1 cells, as demonstrated by decreased insulin-induced 473Ser AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large number of previous studies has also reported enhanced protection by polyphenols on RBC [36]. Plant-derived phenols are reported to have a broad spectrum of free-radical scavenging, antioxidant and protective activities [37][38][39][40][41]. In other studies red wine polyphenols, containing 3.5 mM gallic acid equivalent (GAE) of phenolic compounds, prevented oxidative modifications on the RBC system, such as haemolysis and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…There are experiment-based evidence for the existence of erythrocyte e-transport transmembrane chain related to transferrin receptor (Orringer and Roer, 1979;Goldenberg et al 1990), that is known to reduce K 3 Fe(CN) 6 and removes protons from inside the cell through the cell membrane (Low et al 1987). Our own experiments showed that K 3 Fe(CN) 6 inhibits 59 FeLF binding to erythrocytes (Maneva et al 2003) as most probably Lf and K 3 Fe(CN) 6 compete for one and the same electron formed in oxidative phosphorylation in glycolysis; Lf is the physisological activator of the signal pathway used by ferricyanide that leads to tyrosine phosphorylation of band 3 and consequent glycolysis activation.…”
Section: Control Over Glycolytic Enzymesmentioning
confidence: 95%
“…Our previous studies showed that Lf binding with erythrocyte membrane receptors (Taleva et al, 1999) results in stimulation of glycolysis, antioxidative protection (Maneva et al, 2003) and activation of Na + /K + -ATPase activity (Maneva et al, 2007). Lf-receptor interaction might intervene in short-term effects of regulation, involving processes of changes in association, phosphorylation and oxidation of the membrane proteins.…”
Section: Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation